Reluctance to initiate cooperation: the trade-off between effectiveness and hesitation in the sequential one-shot prisoner's dilemma - Hirofumi Hashimoto; Kanako Naganobu; Kaede Maeda; Shigehito Tanida (Frontiers in Behavioral Economics)
Previous research suggests that initiating cooperation in a sequential one-shot prisoner's dilemma fosters mutual cooperation. We hypothesized that sense of control, defined as the belief that one's cooperative decision will be reciprocated, plays a crucial role in fostering mutual cooperation. To test this, we conducted two experiments comparing three conditions. In the simultaneous condition, both players made their decisions at the same time. In the self-first condition, participants made their decisions first in a sequential setting. In the other-first condition, they made their decision after observing their partner's choice. The results indicate that initiating cooperation increases the likelihood of mutual cooperation. However, participants were reluctant to be the first to cooperate, despite its effectiveness. Our paper discusses these findings from a cross-cultural psychological perspective, highlighting potential differences in cooperative behavior across cultural contexts.